HPLC-DAD-ESI/MS phytochemical investigation, antioxidant, and antidiabetic activities of Moroccan Rosa canina L. extracts - Mourabit, Yassine; El Hajjaji, Souad; Taha, Douae; Badaoui, Bouabid; El Yadini, Meryem; Rusu, Marius Emil; Lee, Learn-Han *; Bouyahya, Abdelhakim; Bourais, Ilhame (Elsevier, 2023)
The aim of this study was to determine the phenolic composition and evaluate the biological properties of Rosa canina L. fruits. Three extraction methods (ultrasonic, maceration, and Soxhlet) were used to prepare the methanolic extracts. LC-MS analysis detected new phenolic compounds including phenolic acids (cinnamic acid, p-coumaric acid, ferulic acid), flavonols (quercetin glucoside, quercetin-glucuronide, quercetin-pentoside, kaempferol-glucoside), and hydrolyzable tannins (digalloylglucose, pyrogallol-2-O-glucuronide). According to Folin-Ciocalteu test, the TPC values were 138.47, 141.10, and 140.49 mg GAE/g extract for ultrasonic, maceration, and Soxhlet method, respectively. This phenolic richness was confirmed by the antioxidant power tests and FRAP assay. The ultrasonic extract presented IC50 of 30.12 μg/mL for the DPPH test, the Soxhlet extract had a concentration of 264.33 μmol TE/g extract for the ABTS test, and the maceration extract showed a level of 87.26 mg AAE/g extract, according to the FRAP assay. The anti-diabetic activity was determined by an α-amylase inhibition test. Based on this test, R. canina fruits revealed a significant antidiabetic activity (65.28%) for the ultrasonic extract at a concentration of 250 μg/mL. In conclusion, the hips of R. canina could be a natural source of potentially useful bioactive compounds for the treatment of type 2 diabetes and oxidative stress.